Microchannel network hydrogel induced ischemic blood perfusion connection - Jung Bok Lee (Nature Portfolio, 2020)
Restoration of blood flow to damaged sites has commonly involved treatment with pro-angiogenic molecules but these have undesired side effects. Here the authors present a microchannel-patterned gelatin hydrogel that is able to rescue mouse and porcine models of hindlimb ischemia.